Edges of the Lord - Braun, Zev; Bogayevicz, Yurek ([United States] : Miramax Home Entertainment, 2005)
Romek is a Jewish boy from Krakow hiding out with a rural Catholic family in Poland in 1943. Romek soons finds himself in an ackward position with the other children of the village, who don't know whether to view the newcomer as a friend or rival. In a catechism class taught by a local priest, Ramek meets Marka, a local thirteen-year-old whose romantic interest sparks some twists that include betrayal, murder, and revenge with religious overtones
Executive producer, Danny Dimbort ; writer, Yurek Bogayevicz
Starring: Haley Joel Osment, Willem Dafoe
VCD format
Keywords: Adventure films; Jews in motion pictures; War films